How much can asset transfers help the poorest? Evaluating the results of BRAC's ultra-poor programme (2002–2008) - Krishna, Anirudh; Poghosyan, Meri; Das, Narayan Chandra (Taylor and Francis, 2022)
This article was published in The Journal of Development Studies [©2012 Rights managed by Taylor & Francis] and the definite version is available at: ttps://doi.org/10.1080/00220388.2011.621942 The Article's website is at: https://www.tandfonline.com/doi/full/10.1080/00220388.2011.621942?scroll=top&needAccess=true